Rethinking Indonesia's Legal System - Al Habibi, Abdul Zaky; Erva Dyana Puri; Fadlan Muhajir; Nasution, Hadi Pratama; Khairani; Tasya Aulia (Getpress Management Journals, 2024)
This research aims to explore the legal system in Indonesia which is formed from various legal sources. The main issues raised are how this diverse legal system can maintain social order and provide legal certainty, as well as how the current positive law (ius constitutum) can adapt to ongoing social changes. This study uses a literature study method with an approach to Indonesian legal history, which traces the development of the legal system from the colonial period to the modern era. Data was obtained from primary and secondary literature, such as laws, books, journal articles, theses, and relevant news. The analysis was carried out with the stages of data triangulation to ensure the accuracy and validity of the research results. The findings of this study show that the legal system in Indonesia is a dynamic and complex system. Positive law has a central role in providing legal certainty, but challenges arise when the applicable law is no longer relevant to the needs of society. Therefore, it is important to carry out adaptive legal reforms, strengthen law enforcement, and increase public legal awareness so that the Indonesian legal system is able to present justice and order in accordance with the times.